Determinants of environmental quality, economic growth, and income inequality in Indonesia: a panel econometric analysis across provinces - Mira Hastin (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2026)
The imperative to decouple economic growth from environmental degradation is paramount for sustainable development, especially in emerging economies. This study investigated the integrated determinants of environmental quality in Indonesia, focusing on the roles of economic structure, social factors, and institutional governance. A mixed-methods approach was employed, combining a two-way fixed effects panel regression and a Panel Vector Autoregression model on provincial data (2013–2023) with expert interviews. The analysis provides evidence consistent with an Environmental Kuznets Curve relationship and indicates that institutional quality plays a central conditioning role in shaping this trajectory. The shadow economy exerted a significant negative pressure, while human development showed a positive association. Crucially, the results indicate a bidirectional dynamic relationship between economic growth and environmental quality. The findings suggest that stronger local governance is associated with lower environmental costs of development and that improvements in environmental quality may support longer-term economic resilience. The study concludes that integrated policies strengthening institutions, formalizing the economy, and investing in human capital are critical for sustainable development in Indonesia and similar contexts.